Financial analysis for selected land use options in Malaysian agroforestry system / Ahmad Fauzi Puasa, Huda Farhana Mohamad Muslim and Najib Lotfy Arshad - Puasa, Ahmad Fauzi; Mohamad Muslim, Huda Farhana; Arshad, Najib Lotfy (Universiti Teknologi MARA Cawangan Pahang, 2006)
Agroforestry or farm forestry is a production technique that combines agriculture and forestry on the same piece of land to fully utilise the natural resources of sunlight, water and nutrition. This study focuses on developing several agroforestry cropping systems and land use options, and secondly, estimating the costs and benefits of each of the cropping system. Results show that cost depends on the cropping system design. To some extent, soil erosion and carbon-sink were incorporated in the analysis as well. Based on the costs and benefits estimated, the most profitable cropping pattern and land use options were chosen. Agroforestry projects can contribute to the supply of woods as well as food to the country. The success of agroforestry is largely determined by the extent to which individual forest and agricultural components can be integrated to benefit rather than hinder one another. The choice of trees and crop species combinations are important when setting up the system.